Existence criteria and classification schemes for positive solutions of second-order nonlinear difference systems - Wan-Tong Li; Can-Yun Huang; Sui Sun Cheng (Discrete Dynamics in Nature and Society)
Classification schemes for positive solutions of a class of second-order nonlinear difference systems are given in terms of their asymptotic magnitudes; and necessary as well as sufficient conditions for the existence of these solutions are also provided. Finally, some examples are given to illustrate the main results.